Quantitation of Total Oil Contents, Proteins and Fatty Acids Composition in Fruits of Pistacia Species and Their Hybrids Growing in Turkey. - Suzerer, V.; Onay, A.; Kizmaz, V.; Calar, N.; Uncuoglu, A. A.; Boukeloua, A.; Ilikcioglu, E. (Springer, 2015)
[No abstract available]
In Vitro Biology Meeting -- MAY 30-JUN 03, 2015 -- Tucson, AZ